Pengembangan Media Pembelajaran Berbasis Video Tutorial Materi Bolabasket (Shooting Skill) untuk Siswa Kelas XI SMA: Pengembangan Media Pembelajaran Berbasis Video Tutorial Materi Bolabasket (Shooting Skill) untuk Siswa Kelas XI SMA - Mahardika, I Putu Adi; Semarayasa, I Ketut; Satyawan, I Made (Universitas Pendidikan Ganesha, 2024)
This study aims to optimize the learning process more than before. This study uses a development study approach with the ADDIE model consisting of five stages, namely analysis, design, development, implementation, and evaluation. The developed product has been validated by experts in the fields of educational content, learning design, learning media, and field practice. Product trials include individual trials on three students, small group trials on nine students, and large group trials on twenty-seven students. Data were collected using a questionnaire and analyzed using quantitative descriptive analysis. The results showed that the validation of learning content experts produced a score of 96%, a very good category, validation of learning design experts produced a score of 96%, a very good category, validation of learning media experts produced a score of 95%, a very good category, validation of field practitioners produced a score of 96%, a very good category, individual trials produced a score of 98%, a very good category, small group trials produced a score of 96%, a very good category, and large group trials produced a score of 90%, a very good category. Therefore, the product developed, namely video tutorial-based teaching materials for basketball material (shooting skills), functions as a learning resource that can improve the quality of learning during the learning process.